Edukasi Kesehatan Tentang Pencegahan dan Pengendalian Penyebaran Covid-19 Di Tatanan Sekolah Pada SiswaSiswi SMK Kesehatan - Meda Yuliani; Ika Kurnia Sukmawati; Irfan Safarudin Ahmad; Desi Fitriani Kuswara; Asri Kartika Sumirat; Elsa Ratna Dewi; Lilis Rismayanti; Aradea Amanda (Jurnal Pengabdian Ahmad Yani, 2021)
Abstract The world and including Indonesia are still shocked by cases of corona virus infection that continue to infect. In Indonesia, currently cases of patients dying from the corona virus have reached 105,598 (as of August 7, 2021). Since the corona virus (COVID-19) is rapidly spreading, it's currently considered a pandemic. Schools and students must be educated about the corona virus (also known as Covid-19) and clean and healthy living habits in order to comply with health standards under the new normal school order, which is now in place for face-to-face interactions. This community service project aims to educate students at the Health Vocational School about clean and healthy living and the role it plays in preventing and managing the development of COVID-19 in school settings in order to offer health protocols education to them. The present face-to-face function of preventing and regulating the spread of COVID-19 in educational settings. There were 158 students participating in the activity, which was conducted online on August 14, 2021, using the Zoom Meeting software. Lectures, debates, and instructional video screenings are some of the methods used. Students' awareness of clean and healthy living behaviors and their role in preventing and regulating the spread of COVID-19 has increased as a consequence of the study, particularly in educational settings. To prevent the spread of the corona virus, it is recommended that the school recall and monitor children constantly. Keywords: covid-19, health education, prevention, control, Vocational Students. Abstrak Kasus infeksi virus corona terus terdengar masyarakat di seluruh dunia, khususnya di Indonesia. Saat ini ada 105.598 orang Indonesia yang meninggal akibat virus corona (per 7 Agustus 2021). Karena penyebarannya yang cepat, virus corona (COVID-19) kini telah menjadi wabah yang ditakuti oleh seluruh umat manusia. Sekolah dan siswa harus dididik tentang virus corona (juga dikenal sebagai Covid-19) dan kebiasaan hidup bersih dan sehat untuk mematuhi standar kesehatan di bawah tatanan sekolah normal baru, yang sekarang berlaku untuk kontak tatap muka. . Meskipun siswa SMK Kesehatan mengetahui tentang peraturan kesehatan, proyek pengabdian masyarakat ini masih perlu mendidik mereka tentang hidup sehat dan peran yang dapat dimainkan oleh hidup bersih dan sehat dalam menghindari dan mengendalikan penyebaran COVID-19 di lingkungan sekolah. hadirnya fungsi tatap muka pencegahan dan pengaturan penyebaran COVID-19 di lingkungan pendidikan Ada 158 siswa yang mengikuti kegiatan yang dilakukan secara online pada 14 Agustus 2021 dengan menggunakan software Zoom Meeting. Ceramah, debat, dan pemutaran video instruksional adalah beberapa metode yang digunakan. Kesadaran siswa tentang perilaku hidup bersih dan sehat serta perannya dalam mencegah dan mengatur penyebaran COVID-19 meningkat sebagai konsekuensi dari penelitian, khususnya di lingkungan pendidikan. Untuk mencegah penyebaran virus corona, disarankan agar sekolah memanggil dan memantau anak-anak secara terus-menerus. Kata kunci: covid-19, edukasi kesehatan, pencegahan, pengendalian, Siswa-siswi SMK.